Perbandingan Hukum Perkawinan Nasional dan Hukum Adat Merariq di Lombok: Antara Legalitas dan Legitimasi Sosial - Achmad Dirham Ghozali Boer; Putri Aulia Zahra Qurbany; Salomo Mharon Jhonatan Gultom; Dwi Desi Yayi Tarina (Media Hukum Indonesia (MHI), 2026)
One customary practice that continues to exist is the merariq tradition in Lombok, West Nusa Tenggara, which regards marriage as a form of social legitimacy achieved through the process of a man “eloping” with a woman. This study aims to analyze the comparison between national marriage law as regulated under Law Number 16 of 2019 and the customary practice of merariq, as well as to examine the potential conflicts of norms arising between them. The research employs a normative legal research method using both statutory and conceptual approaches. The findings indicate that there are fundamental differences between national law, which emphasizes formal legality, consent, age requirements, and administrative procedures, and customary law, which focuses on social legitimacy and cultural values. These differences have the potential to create legal uncertainty and vulnerabilities in the protection of rights, particularly for women and children. Therefore, efforts to harmonize national law and customary law are necessary to establish a family law system that is more responsive to social realities while upholding the principles of justice and legal protection